The Significance of Computer Forensics in Electronic Documents as Evidence in Criminal Law - Aris Hardinanto; Barda Nawawi Arief; Joko Setiyono (Faculty of Law, University of Merdeka Malang, 2023)
Forensic science standards, no crime never leaves traces. Along with the emergence of cybercrime, a new type of evidence emerged as an expansion of conventional evidence in Indonesian criminal procedural law, namely electronic evidence as stated in the Law on Electronic Information or electronic documents whose authenticity can be guaranteed, but there is no further explanation. Further, what is the procedure for guaranteeing its authenticity? Based on this, not all electronic information or documents can be used as evidence. One branch of forensic science that is relevant to proving cybercrimes is computer forensics. The problem that arises is to what extent is the significance of computer forensics to guarantee electronic information or electronic documents as evidence. This article was based on legal research using a conceptual, statutory, and case approach. The result of this study is that computer forensics plays a significant role in the crime of illegal access to electronic devices because it is a tool in criminal procedural law that can be used to guarantee the authenticity of electronic information or electronic documents so that they can be accepted as evidence in court.How to cite item: Hardinanto, Aris, Barda Nawawi Arief, and Joko Setiyono. â€œThe Significance of Computer Forensics in Electronic Documents as Evidence in Criminal Law.â€ Jurnal Cakrawala Hukum 14 no. 2 (2023):155-166. DOI: doi.org/10.26905/idjch.v14i2.10820.